(untitled) (Bangladesh Journal of Scientific Research, 2016)
Severe anthracnose symptom was recorded on the leaves of five angiosperms during September to November, 2010. In total nine species of fungi belonging to four genera of the class deuteromycetes and a sterile fungus were found to be associated with the infected leaves of Abelmoschus esculentus (L.) Moench, Cucurbita maxima Duchesne, Datura metel L., Gossypium hirsutum L. and Vigna sinensis L. The associated fungi were Aspergillus flvaus Link, A. fumigatus Fresenius, A. nidulans (Eidam) G. Winter, A. niger van Tiegh, Cercospora sp., Colletotrichum capsici (Syd.) Butler & Bisby, Colletotrichum dematium (Pers.) Grove, Colletotricum gloeosporioides (Penz.) Penz. and Sacc., Curvularia clavata Jain, and a sterile fungus. Bangladesh J. Sci. Res. 28(2): 103-111, Dec-2015